Human Resource Practices and Employee Retention in Local Governments in Uganda: A Case of Kabale District Local Government. - Baingana, Alex (Kabale University., 2024)
This study examined the effect of human resource practices on employee retention in Local Governments; a case of Kabale District Local Government. The study was guided by three study objectives which included examining the effect of recruitment and selection practices on employee retention at KDLG, the effect of training and development on employee retention at KDLG, and the effect between human resources compensation and benefits on employee retention at KDLG. A case study research design was used considering utilizing both quantitative and qualitative approaches. The study targeted 134 participants, but 119 managed to respond, including 117 who filled out the questionnaire and 02 who were interviewed. The study findings revealed that there was a very insignificant relationship between recruitment and selection on employee retention at (r = .026, P=0.781 > 0.01), there was a positive but insignificant relationship between development and training and employee retention at (r = .159, P=0.86 >0.01) and there was a positive and significant relationship between compensation and benefits and employee retention at (r = .430**, P=0.00 <0.01). From the linear regression analysis, it was revealed that from the linear regression, it was revealed that recruitment and selection predicted employee retention by only 0.08% with insignificant predictive potential at (Beta = .026, p=.781>0.05), development and training predicted employee retention by only 10.1% with insignificant predictive potential at (Beta = .159, p=.086>0.05) and compensation and benefits predicted employee retention by only 17.8% with significant predicator at (Beta = .430, p=.000<0.05). From the multiple regression analysis, the combined constructs of human resource practices with constructs of recruitment and selection, development and training, and compensation and benefits collectively accounted for 18.8%. However much recruitment and selection positively predicted employee retention at KDLG, it was an insignificant predictor at (Beta = .049, p=.623>0.05) and despite development and training positively predicting employee retention at KDLG, it was an insignificant predictor at (Beta =.227, p=.07 >0.05). Furthermore, compensation and benefits positively and significantly predicted employee retention at KDLG at (Beta =.567, p=.000 <0.05). The study recommended that it is crucial for KDLG to reevaluate its retention strategies, focusing on enhancing job satisfaction, professional development opportunities, and overall workplace conditions to mitigate turnover and ensure the retention of valuable talent. It was also recommended that KDLG reassess its approach to employee development through benchmarking and hiring professional trainers to ensure equitable access to training opportunities, establishing regular and comprehensive training programs, and fostering a culture that prioritizes continuous learning and professional growth. Failure to address these deficiencies will continue to impede efforts to retain talent and hinder the district’s effectiveness. There is also a need for providing competitive salaries, ensuring all employees are on the payroll, offering comprehensive workplace allowances and recognition programs, and equitably distributing work benefits across employees at all levels.